State Variation in TANF Expenditures: Implications for Social Work and Social Policy. Issue 2 (16th April 2021) - Fusaro, Vincent A.
Abstract: The Temporary Assistance for Needy Families (TANF) program is a federal block grant to the states, with a required state contribution. Although often viewed as a cash assistance program with work requirements and services targeted at extremely low-income families with children, only about one-quarter of all state and federal TANF funds are now used for traditional cash aid. Uses of funds vary widely by state, and alternatives range from refundable tax credits to support of state child welfare systems. In this article, the author examines the relationship between state categorical TANF spending and key social, political, and economic characteristics using data from 2015 to 2017 and multilevel linear models. Racial and ethnic demographics of the cash assistance caseload are associated with differences in spending, with states with larger proportions of the caseload composed of people of color devoting a lower percentage of effort to traditional benefits and more to alternative cash transfers. Changes in unemployment rate within states are associated with greater spending on basic assistance and reduced spending on alternative transfers. These findings indicate that, although TANF cash benefits spending may be economically responsive within the program's overall flexible structure, spending patterns raise issues of equity for disadvantaged families.